(3QSGdI aj YdGeGJ GdbjGeIs - (3Ydj Hf (B((3SdWGf(B) (3eMeO, fhQ GdOjf GdedG GdgQhj GdbGQj,J (B1014 (3g` s
(3ChdgG (B:s
(3GdMeO ddg GdPi CXgQ GdBjGJ GdhGVMGJ ai cdGeg GdbOje CeG HYO ajbhd Cf GdMHQ ehdGfG GdbGVi GdHjVGhi bGd ai JaSjQ bhdg JYGdi (B:- " (3gd jfXQhf (B" s
(3BNQgG (B:s
(3bGd QShd Gddg Udi Gddg Ydjg hSde (B:" (3GdBjGJ HYO GdeCJjf (B" (3hGdXGgQ hGddg CYde Cf jchf GdeQGO HGdeCJjf HYO GdCda GdJJGHY dcf gd GdeQGO HGdBjGJ eWdb ETQGW GdSGYg GdTeS ef eZQHgG SHMGfg hJYGdi CYde s
(3Vef eLehY , JQJjHgG (B: (3GdcJGH (B20s
(3eTJedI Ydi GdcdGe Ydi JaSjQ BjI ef JaSjQ GdHjVGhis
(3HgG fXGe GdJYbjHIs
(3GdJhKjbGJ GdeQLYjI (B:s
(3GdCYdGe ; NjQ GdOjf GdRQcdj (B, (3J (B1396 (3g` (B/ 1976(3e(B: (3L (B5 - (3U (B12 ; (3eYLe GdeDdajf ; YeQ QVG cMGdI (B, (3J (B1408 (3g` (B/ 1987 (3e(B: (3L (B7 - (3U (B100s
(3eUOQ GbJfGA GdCUd (B:s
(3OGQ GdcJH GdeUQjI (B((3eLGejY JjehQ (B136) s
Keywords: (3GdeLGejYs